Persistence of Campylobacter and Salmonella in the Ceca, Spleen and Liver/gallbladder of Inoculated Broilers - Cox , N.A.; McLendon, B.L.; Wilson, J.L.; Hofacre, C.L.; Berrang, M.E.; Hinton, Jr, A.; Cosby, D.E. (International Journal of Poultry Science, 2018)
Background and Objective: Poultry is a major source of Salmonella and Campylobacter involving human illness. Several body openings of the young chick are exposed to bacteria. The objective of this study was to determine how long artificially inoculated Salmonella or Campylobacter persist in the ceca, spleen and/or liver/gallbladder of broilers. Materials and Methods: Day old chicks (10/isolation unit and 5/floor pen) were orally gavaged with 103 cells of either a marker Salmonella Typhimurium or a marker Campylobacter coli and ceca, spleen and liver/gallbladder were aseptically sampled. Results: All organs from all birds were positive for Salmonella Typhimurium and C. coli at 1 week, most were still positive at 2 and 3 weeks. By 6 weeks, no Salmonella Typhimurium was detected in any tested organs. By 6 weeks all ceca and spleens were positive for Campylobacter coli but none found in liver/gallbladder samples. Conclusion: Translocation of Campylobacter and Salmonella to internal organs and their persistence in these organs are important because these bacteria will not be detected by the currently used methods. Current methods sample the intestinal tract only with drag swabs or fecal samples. Research is needed to understand translocation and persistence of both Campylobacter and Salmonella in poultry.